A review of coconut varieties in Malaysia / Nur Aziatul Fazdlin Ab Rahman and Shamsiah Abdullah - Ab Rahman, Nur Aziatul Fazdlin; Abdullah, Shamsiah (Faculty of Plantation and Agrotechnology, 2018)
Cocos nucifera L. is one of the world’s valuable crops, known as the ‘tree of a thousand uses’ since every part of the coconut tree can be processed into many products. Coconut is well distributed throughout the Asia including Malaysia and Indonesia. In Malaysia, coconut is considered important which ranked as the fourth important crop after oil palm, paddy and rubber. However, for the past few years, the production of the coconut seems to be declined because of the competition with, oil palm for acreage of cultivation area. A review on the varieties of coconut Malaysia was carried out to provide source of references and information which can assist the selection of good coconut varieties for cultivation and breeding program. Generally, there are 16varieties of coconut in Malaysia, classified into three main types; tall, dwarf and hybrid that are registered under Department of Agriculture in 2013. From the 16 varieties, MATAG hybrid is seen to be profitable to be cultivated because of the characteristics such as early bearing, semi dwarf tree and abundant fruits per bunch with large fruits size which can give high production to the fanners. Malayan Yellow’ Dwarf and Malayan Red Dwarf also have high potential for breeding program due to due to an early bearing that contribute to the high fruits production with the average of 25000-30000 fruits per hectare for every year compare to Malayan Tall which only produce 6000-8000 fruits per hectare for every year. Although the fruits is small in size, M YD and MRD have a great potential to be commercialized for young coconut water drink. Pandan variety is very synonym with the pandan aroma that become the added value to the selection of potential parent for breeding programme.